M cells of mouse and human Peyer's patches mediate the lymphatic absorption of an Astragalus hyperbranched heteroglycan. (15th November 2022) - Zhang, Quanwei; Hao, Shuang; Li, Lifeng; Liu, Man; Huo, Chuying; Bao, Wanrong; Cheng, Huiyuan; Fung, Hauyee; Wong, Tinlong; Wu, Wenjie; Leung, Pingchung; Wang, Shunchun; et al.
Abstract: The gut cell wall is considered an impenetrable barrier to orally administrated polysaccharides. We recently reported a selective lymphatic route for Radix Astragali polysaccharide RAP to enter Peyer's patches (PPs) to trigger immune responses. However, how RAP enters PPs is unclear. Herein, we screened the intestinal epithelial cells of mice and found that the follicle-associated epithelium cells were specifically bound with FITC-RAP. Further studies in vitro and in vivo revealed that RAP was efficiently transported by microfold (M) cells. We also confirmed that M cell-transported RAP directly contacted dendritic cells. More importantly, for the first time, we verified this interesting M cell-mediated transcytosis of RAP in the human distal ileum. Mechanistically, we identified M cells to be the transporter cells that independently deliver RAP into the lymphatic system to trigger immune responses. This interesting transcytosis mechanism might apply to many other immunomodulatory polysaccharides orally dosed to human body. Graphical abstract: Unlabelled Image